Chromosomal abnormalities during microsporogenesis in two varieties of cassava Manihot esculenta Crantz (2015)
Abstract The cassava crop Manihot esculenta crantz is the third resource more important to provide calories to the population in the marginal tropical countries of Africa, Asia and South America. However, socioeconomic factors, market conditions, pest, diseases, biotic and abiotic constraints affect cassava production of smallholders. Multiple efforts in cassava breeding program have been made, but his high heterozygous and strong inbreeding depression difficult the production of homozygous parental, causing that conventional crossings lead to a time large. For this reason the doubled haploid technology by isolated microspore culture for production of homozygous plant is an interesting alternative, reducing time and cost in hybrid production. This study was conducted in the International Center of Tropical Agriculture, we assessed cytology and cytogenetic features of microspores tetrads in TMS60444 and SM1219-9 cassava genotypes for optimize efficient protocols of doubled haploid production through evaluation of meiotic abnormalities, meiotic index and viability in microspore tetrads of donor plant used for doubled haploid production. Abnormalities during microsporogenesis like multiple nucleoli, sticky chromosomes, micronuclei, irregular spindles, dyads, triads and polyads were evidenced although in a low frequency. However, the great level of meiotic index and high microspore viability lead to conclude that these cassava genotypes are meiotically stable and can be used in breeding programs or conservation strategies.